2020
DOI: 10.1155/2020/9650251
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Hydropower Generation and Rainfall-Gauged and Ungauged Catchments from Sri Lanka

Abstract: The relationship between the rainfall and minihydropower generation in a catchment is highly nonlinear. Therefore, the prediction of minihydropower generation is complex. However, the prediction is important in optimizing the control of electricity generation under various environmental conditions. Ongoing climate variabilities have completely changed the minihydropower generation to some parts of the world, and it is significant. Therefore, this paper presents results from two soft-computing studies in search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…erefore, it could be analytically proved with evidence that out of the four prediction models developed in this study, the GPR has shown excellent performance and even outperformed all the models cited here. In particular, in the previous study conducted on the Samanalawewa hydropower generation, only the ANN was applied, and the performance was evaluated only in terms of the correlation coefficient and the MSE [6]. All the ANN-based prediction models were found Mathematical Problems in Engineering less accurate than the GPR-based model presented in this paper.…”
Section: Quarterly Models Developed Based On Four Meteorological Factors Tablementioning
confidence: 82%
See 1 more Smart Citation
“…erefore, it could be analytically proved with evidence that out of the four prediction models developed in this study, the GPR has shown excellent performance and even outperformed all the models cited here. In particular, in the previous study conducted on the Samanalawewa hydropower generation, only the ANN was applied, and the performance was evaluated only in terms of the correlation coefficient and the MSE [6]. All the ANN-based prediction models were found Mathematical Problems in Engineering less accurate than the GPR-based model presented in this paper.…”
Section: Quarterly Models Developed Based On Four Meteorological Factors Tablementioning
confidence: 82%
“…However, Beheshti et al [5] expressed reservations on the uncertainties in predicting reservoir variables and hydropower under climate scenarios and suggested further studies, taking the variability in water allocation for irrigation into account. In addition, the complex nonlinear relationship between the rainfall and minihydropower generation in gauged and ungauged catchments of Sri Lanka has been studied recently using ANN, which showed a good correlation between them at the gauged catchments compared to ungauged catchments [6]. Based on the correlation values between the observed and predicted energies, Abdulkadir et al [7] justified the use of neural network approaches in modelling the hydropower generation as a function of reservoir variables at two reservoirs along the River Niger in Nigeria.…”
Section: Introductionmentioning
confidence: 99%